Customer Loyalty among the Generation Y Customers in the Fast Food Industry - Mariady, Hansen (2011)
Nowadays, the level of competitiveness of the fast food industry in Malaysia is intense. New competitors are emerging and current players in the market are striving to increase their market share through opening new branches in different parts of cities. The key target market for these companies would be the Generation Y customers due to their lifestyle and consumption habits. In order to be competitive in the industry, fast food companies should venture into instilling customer loyalty in the hearts of the consumer as it cost lesser and has the long-term benefits in term of profitability. Therefore, this research would aim to investigate the factors which would affect the enhancement of customer loyalty among the Generation Y customers in Malaysia. Besides that, this research would also investigate the effect of customer satisfaction as the mediating variable between those factors and customer loyalty. As Malaysian fast food companies is situated in many different towns with different population, this research would also compare the perception of factors which are important to customer loyalty between two towns which have different populations. The factors chosen for this research are food quality, price, service quality, environment and location. According to the results, the factors which have significant effect on both sets of respondents are the food quality, service quality environment factor. Therefore, it can be deduced that these are the factors which affect the overall Generation Y customers in terms of their customer loyalty. The data also shows that customer satisfaction factor mediates the relationship between these factors and customer loyalty.